The Implementation of Science Interconnection for Fiqh Subject at MTs MIM Langsa Aceh - Hamdani Hamdani; Zainul Lian Malik Hasibuan; Husaini Husaini; Mawardaniah Mawardaniah (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study aims to describe the implementation of the science interconnection approach in learning Fiqh carried out at Madrasah Tsanawiyah Swasta Islam Modern (MTs MIM) Langsa Aceh. This study uses a qualitative research approach. Meanwhile, data collection was carried out through in-depth observation and interview techniques. After the data is collected, the writer sorts the data, presents the data, and draws conclusions. The results showed that the teachers of Jurisprudence at MTs MIM  Langsa applied the interconnection approach of Jurisprudence subjects with subjects related to other subjects and connected to learning resources that utilized the sophistication of information technology. The interconnection approach applied at Madrasah Tsanawiyah Langsa Aceh succeeded in re-knitting various religious and scientific subjects that previously occurred in a scientific and teaching dichotomy.